Organizational assimilation and demographics - Overby, Amy T. (University of Wisconsin--Whitewater, 2010)
Fine (1996) argues that the most pressing challenge of our time is the challenge created by the increasing cultural diversity of the U.S. workforce. Despite this statement, and statistics which project a nearly 20% increase in the minority workforce from 18% to 37% during 1980-2020 (Nat’l Center, 2005), there is limited research on how a member’s race-ethnicity affects perceived levels of organizational assimilation. Weick’s (1979) Organizational Information Theory (OIT) was used to assess factors that may lead to information equivocality and lower degrees of assimilation for people of color in the workplace. This study analyzed the responses of organizational members who completed a survey questionnaire designed to determine if equivocality affects their perceptions of assimilation. Equivocality prevents organizations from functioning effectively and achieving their goals. Hofstede’s (1991) cultural dimensions: 1) power distance, 2) individualism, 3) masculinity, 4) uncertainty avoidance, and 5) long-term orientation, racial-ethnic cultural identification (Cox, 1993), and assimilation dimensions (familiarity with others, acculturation, recognition, and involvement) (Myers and Ozetel, 2003) were used to examine racial-ethnic differences in assimilation of people of color versus their White counterparts. Three conclusions are offered. First, assimilation was significantly and positively correlated to the convergence of perceptions of the importance of collectivism by individuals and their employer organizations. Second, differences in perceptions of the employee’s value of collectiveness and the organization’s value of it were positively related to equivocality. Finally, and contrary to expectations, people of color with high racial identification reported feeling more acculturated to the organization than their White counterparts with low/medium racial identification. The National Center for Public Policy and Higher Education (2005) projects that by 2020, 37% of U.S. workers will consist of Americans whose racial/ethnic origins are African, Hispanic, Asian, Native, and Pacific Islander, and those of mixed race/ethnicity. If organizations are going to be successful in an environment that is no longer majority White, they must have a goal to successfully assimilate members of all racial/ethnic backgrounds.
This file was last viewed in Microsoft Edge.
Keywords: Diversity in the workplace--United States; Multiculturalism--United States; Minorities--Employment--United States; Corporate culture--United States